Effects of Red Pitaya (Hylocereus polyrhizus) on Lipid Profile of Male White Rats (Rattus norvegicus) Receiving High Fat Diet - Werdiningsih, Wiwik; Suhartati, Suhartati (Folia Medica Indonesiana, 2018)
Red dragon fruit (Hylocereus polyrhizus) peel contains anthocyanin, fiber and vitamin C, so it can be used to improve lipid profile in dyslipidemia. The peel of the dragon fruit is not durable, so in this study we used freeze-dried dragon fruit peel. The aim of this study was to prove that the administration of the red dragon fruit peel in a dose of 0.72 g/200 g BW, 1.08 g/200 g BW, and 1.44 g/200 g BW of rat per day for 28 days may improve lipid profile in male wistar strain white rats with high-fat diet. Lipid profiles were studied by examining of total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides. This was a pure experimental study using randomized post test only control group design. This study used experimental animal of 30 male wistar strain white rats which were divided into five groups. Measurements of total, LDL, and HDL cholesterol levels were done by CHOD-PAP method, while triglyceride level was measured with GPO-PAP method. Data were analyzed statistically by One Way Anova test. The results of this study indicated that giving the peel of red dragon fruit as much as 0.72 g lowered total cholesterol levels, 1.08 g lowered total and LDL cholesterol levels, and 1.44 g lowered total cholesterol, LDL cholesterol, triglyceride levels, and raised HDL cholesterol level. Red dragon fruit peel can be used alternatively to improve lipid profile in dyslipidemia.